On the discrete spectrum of a linear operator pencil arising in transport theory - Cojuhari, P. A. (Methods of Functional Analysis and Topology, 2014)
We study the problem of the finiteness of the discrete spectrum for linear operator pencils occurring in one-velocity transport theory. The results are obtained using direct methods of perturbation theory for linear operators. The proposed approach allowed to give a relatively quick proofs of the main results improving related results obtained previously by K. M. Case and C. G. Lekkerkerker.